The Role of School Administration in Enhancing Intellectual Security in the light of Globalization for 11th and 12th Grades in Wilayat of Sohar in Sultanate of Oman - Alghafri, Ali Salim Rashid; Alajmi, Marwah Saleh Ibrahim (Dirasat: Educational Sciences, 2023)
Objectives: The study's objectives were to determine, from the perspective of the students, how the administration of government schools in the Wilayate of Sohar in the Sultanate of Oman can improve intellectual security in the face of globalization, and to identify whether there are statistically significant differences in the role that are related to the student's gender variable. Methods: The study used the descriptive research method. Accordingly, the research sample consists of (381) students of Grades (11-12) in Sohar state, selected by the appropriate stratified method (males, females). A questionnaire was developed to measure the role of the school administration in enhancing intellectual security in the light of globalization for students, and its apparent truthfulness was verified by presenting it to a group of arbitrators and adjusted in the light of their opinions. The data was entered and then the appropriate statistical processing was carried out using the humanities statistical packages program (SPSS). Results: The level of the sample’s evaluation was at a moderate degree, and there were significant differences between the arithmetic averages due to the gender variable in favor of females. Conclusions: The study suggests that school administrators use plays, artwork, research, and educational articles to instruct and improve student understanding of intellectual security. Also, create a committee at the school devoted to enhancing pupils' intellectual security and educate and train parents on the detrimental impacts of social media and modern technology.